User-centric identity management as an indispensable tool for privacy protection. (1st December 2008) - Leenes, Ronald E.
Informational privacy is under siege on the internet. One particular type of privacy threat relates to our digital personae, the digital representations of our identity. The abundant use of identifiers online facilitates the connection of personal data and behavioural patterns from various sources to the rich digital personae of internet users. These digital profiles can then be used for good (e.g., personalised services) and bad (e.g., discrimination). The negative use of profiles affects fundamental rights and values, but also undermines the individual's capability to maintain different (public) images, which is essential in social life. This paper, after discussing the underlying threats and the regulatory framework, argues that legal instruments are insufficient in countering the current threats. Internet users will have to take an active role in protecting their own identities. The paper explores the role that privacy-enhancing technologies can play in this respect.